Sistem Informasi Bank Sampah di Bank Sampah Enviro’18 - Qonita Fildzah; Cahya Vikasari; Nur Wahyu Rahadi (Politeknik Negeri Cilacap, 2022)
Waste Bank is a business The Enviro'18 entity engaged in the social sector that manages and utilizes waste with the aim of maintaining the environment and welfare in the surrounding community. Processes related to activities that can be carried out in the waste bank, such as customer registration, sales of waste, withdrawal of customer balances, preparation of waste sales reports. There are shortcomings in the waste bank process, where all processes are carried out manually and there is no system to facilitate the process. To overcome this, we need a web-based information system that aims to assist in managing customer data and waste data. Making this system using the System Development Life Cycle method with a prototype model. Based on the results of blackbox testing, it can be ensured that the system created can help make it easier for customers to register and view catalogs and make it easier for waste banks to collect waste data and manage data. Broadly speaking, from the test results, all system functionality can run well. This can be proven in process testing and can also be proven in the questionnaire analysis process which shows the functionality of the system that has been built is considered quite good in supporting the processes that run in the enviro'18 waste bank.